Civil engineering education and training report on The Institution of Civil Engineers' Conference, University of Glasgow, 21-22 September, 1972. (Thomas Telford, 1973)
Papers presented at this conference covered the topics of the role of women in engineering, training, technicians, management and continuing education, mid-career training and higher degrees.